Adhesive sheet, repeatedly bent laminated structure, and repeatedly bent device

By introducing Tetoron mesh#380 into the adhesive layer and controlling its physical properties, the problem of peeling off the adhesive layer under repeated bending conditions is solved, and the durability and moisture and heat resistance of the adhesive sheet are improved.

CN113174209BActive Publication Date: 2025-03-28LINTEC CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202011526152.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-01-27
Filing Date
2020-12-22
Publication Date
2025-03-28
Estimated Expiration
2040-12-22

AI Technical Summary

Technical Problem

When the existing adhesive sheet is used in a repeatedly bending display, the interface between the adhesive layer and the adherend is prone to peel off, resulting in poor durability.

Method used

A small amount of adhesive layer clamped with Tetoron mesh#380 with specific physical properties is used to ensure that the water vapor permeability and energy storage modulus are within a specified range, thereby improving the durability of the adhesive layer.

Benefits of technology

Under high temperature and repeated bending conditions, the interface peeling between the adhesive layer and the adherend is reduced, and the durability and moisture and heat resistance of the adhesive sheet are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113174209B_ABST
    Figure CN113174209B_ABST
Patent Text Reader

Abstract

The present invention provides an adhesive sheet, a repeatedly bent laminated component, and a repeatedly bent device having excellent durability against bending. The adhesive sheet (1) has an adhesive layer (11) for bonding a bendable component (21) and another bendable component (22) constituting a repeatedly bent device (3). The adhesive layer (11) is made to have a thickness of 100 μm, and is sandwiched between two sheets of Tetoron mesh #380. The water vapor permeability measured in accordance with JIS K7129 at 40°C and 90% RH is 150 g / (m 2 · 24h) or more, the storage modulus G'(85) of the adhesive constituting the adhesive layer (11) at 85°C is 0.02 MPa or more and 0.2 MPa or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive sheet for a repeatedly bent device, a repeatedly bent laminated structure, and a repeatedly bent device. Background Art

[0002] In recent years, a bendable display has been proposed as a display body (display) of an electronic device. As a bendable display, in addition to a display that is only curved once, a repeatedly curved display that is repeatedly curved (bent) has also been proposed.

[0003] In the above-mentioned repeatedly bendable display, it is considered that one bendable member (bendable member) constituting the bendable display is bonded to another bendable member using the adhesive layer of the adhesive sheet. However, if a conventional adhesive sheet is used for the repeatedly bendable display, there will be problems in durability such as peeling of the interface between the adhesive layer of the bend portion and the adherend due to repeated bending.

[0004] As the above-mentioned conventional adhesive sheet, for example, there can be cited the adhesive sheet disclosed in Patent Document 1. This adhesive sheet has an adhesive layer composed of an adhesive composition comprising: a (meth)acrylic polymer containing a structural unit derived from a monomer having an aromatic ring structure and a polyrotaxane, and its purpose is to have excellent stress relaxation and durability in optical applications.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2016-155911 Summary of the invention

[0008] Technical Problems to be Solved by the Invention

[0009] However, in the examples disclosed in Patent Document 1, the amount of hydroxyl-containing monomers used as crosslinking points in the acrylic polymer is small, and the amount of crosslinking agent used is also small. Therefore, it is believed that the crosslinking agent is consumed by the crosslinking of polyrotaxanes, and the crosslinking structure of the polyrotaxane and the acrylic polymer is not sufficiently formed. Therefore, the stress relaxation property of the adhesive is not sufficient for use in repeatedly bent displays.

[0010] The present invention has been made in view of the above-mentioned actual situation, and an object of the present invention is to provide an adhesive sheet, a repeatedly-bent laminated structure, and a repeatedly-bent device having excellent durability against bending.

[0011] Technical means to solve technical problems

[0012] In order to achieve the above-mentioned object, first, the present invention provides an adhesive sheet having an adhesive layer for bonding a flexible member and another flexible member constituting a repeatedly bent device, characterized in that the adhesive layer having a thickness of 100 μm is sandwiched between two sheets of Tetoron mesh #380, and the water vapor permeability measured in accordance with JIS K7129 at 40° C. and 90% RH is 150 g / (m 2 · 24h) or more, the storage modulus G'(85) of the adhesive constituting the adhesive layer at 85°C is 0.02 MPa or more and 0.2 MPa or less (Invention 1).

[0013] In the above invention (Invention 1), by making the adhesive layer have the above-mentioned physical properties, when a laminated body formed by bonding one flexible member and another flexible member using the adhesive layer is repeatedly bent at high temperature, or when the laminated body is left in a bent state for a long time, it is difficult for the adhesive layer in the bent portion to peel off at the interface between the adherend and the adhesive layer, and the durability is excellent. In addition, by making the adhesive layer have the above-mentioned water vapor permeability, the resistance to wet heat whitening is also excellent.

[0014] In the above invention (Invention 1), it is preferred that the gel fraction of the adhesive constituting the adhesive layer is 10% or more and 90% or less (Invention 2).

[0015] In the above inventions (Inventions 1 and 2), it is preferred that the adhesive layer has a haze value of 10% or less at 23°C (Invention 3).

[0016] In the above inventions (Inventions 1 to 3), the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer preferably has a storage modulus G'(23) at 23° C. of 0.02 MPa to 0.3 MPa (Invention 4).

[0017] In the above inventions (Inventions 1 to 4), it is preferred that the adhesive constituting the adhesive layer contains a polyrotaxane compound (Invention 5).

[0018] In the above inventions (Inventions 1 to 5), it is preferred that the adhesive constituting the adhesive layer is an acrylic adhesive (Invention 6).

[0019] In the above inventions (Inventions 1 to 6), preferably, the adhesive sheet includes two release sheets, and the adhesive layer is sandwiched between the release sheets so as to be in contact with release surfaces of the two release sheets (Invention 7).

[0020] Second, the present invention provides a repeatedly bent stacked structure, which comprises a flexible member and another flexible member constituting a repeatedly bent device, and an adhesive layer for bonding the one flexible member and the other flexible member to each other, characterized in that the adhesive layer is composed of the adhesive layer of the adhesive sheet (Inventions 1 to 7) (Invention 8).

[0021] Thirdly, the present invention provides a repeatedly bent device, characterized in that it includes the repeatedly bent laminated structure (Invention 8) (Invention 9).

[0022] Effects of the Invention

[0023] The adhesive sheet, the repeatedly-bent laminated structure, and the repeatedly-bent device of the present invention are excellent in durability against bending. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a cross-sectional view of an adhesive sheet according to one embodiment of the present invention.

[0025] Figure 2 This is a cross-sectional view of a repeatedly bent laminated structure according to one embodiment of the present invention.

[0026] Figure 3 This is a cross-sectional view of a repeatedly bent device according to one embodiment of the present invention.

[0027] Figure 4 This is an explanatory diagram (side view) for explaining a static bending test.

[0028] Figure 5 This is an explanatory diagram (side view) for explaining the dynamic bending test.

[0029] Description of Reference Numerals

[0030] 1: Adhesive sheet; 11: Adhesive layer; 12a, 12b: Release sheet; 2: Repeatedly bent laminated member; 21: First flexible member; 22: Second flexible member; 3: Repeatedly bent device; 31: Cover film; 32: First adhesive layer; 33: Polarizing film; 34: Second adhesive layer; 35: Touch sensing film; 36: Third adhesive layer; 37: Organic EL element; 38: Fourth adhesive layer; 39: TFT substrate; S: Test piece; P: Retaining plate. DETAILED DESCRIPTION

[0031] Hereinafter, embodiments of the present invention will be described.

[0032] [Adhesive sheet]

[0033] An adhesive sheet according to one embodiment of the present invention has an adhesive layer for bonding one bendable member and another bendable member constituting a repeatedly bendable device, and preferably a release sheet is laminated on one or both sides of the adhesive layer. The repeatedly bendable device and the bendable member will be described later.

[0034] In the adhesive sheet of this embodiment, the adhesive layer is made into 100 μm thick and sandwiched between two sheets of Tetoron mesh #380. The water vapor permeability measured according to JIS K7129 at 40°C and 90% RH is 150 g / (m 2 · 24h) or more, the storage modulus G'(85) of the adhesive constituting the adhesive layer at 85°C is 0.02 MPa or more and 0.2 MPa or less. The details of the method for measuring the water vapor transmission rate and storage modulus in this specification are shown in the test examples described below.

[0035] By making the adhesive layer of the present embodiment have the above-mentioned physical properties, the durability to bending (hereinafter, sometimes simply referred to as "durability") is excellent. Specifically, when a laminate formed by bonding a flexible component and another flexible component using the adhesive layer is repeatedly bent at high temperature (hereinafter, sometimes referred to as "dynamic durability" or "dynamic durability"), or when the laminate is placed in a bent state for a long time, it is not easy for the adhesive layer in the bent portion to peel off at the interface between the adherend and the adhesive layer. In addition, by making the adhesive layer of the adhesive sheet of the present embodiment have the above-mentioned water vapor permeability, even when the repeatedly bent device is placed under high temperature and high humidity conditions, the moisture that has penetrated into the adhesive layer is easy to escape from the adhesive layer when it is restored to normal temperature and humidity, and it is not easy to produce condensation of moisture, which can inhibit the whitening of the adhesive layer. That is, the adhesive sheet of the present embodiment is excellent in both durability and resistance to moisture and heat whitening.

[0036] From the perspective of durability and resistance to whitening by moisture and heat, the water vapor permeability should be 150 g / (m 2 ·24h) or more, preferably 160g / (m 2 ·24h) or more, particularly preferably 170g / (m 2 ·24h) or more, more preferably 190g / (m 2 On the other hand, from the perspective of durability, the water vapor permeability is preferably 500 g / (m 2 ·24h) or less, more preferably 300g / (m 2 · 24h) or less. Considering the effect of the increase in the hardness of the adhesive layer surface due to the increase in hydrogen bonds on the durability, 250g / (m 2·24h) or less, more preferably 200g / (m 2 24h) or less.

[0037] In addition, from the perspective of durability, the storage modulus G'(85) of the adhesive constituting the adhesive layer needs to be 0.02MPa or more, preferably 0.03MPa or more, particularly preferably 0.04MPa or more, and further preferably 0.05MPa or more. In addition, similarly, from the perspective of durability, the storage modulus G'(85) needs to be 0.2MPa or less, preferably 0.1MPa or less, particularly preferably 0.08MPa or less, and further preferably 0.06MPa or less.

[0038] In addition, the storage modulus G'(23) of the adhesive constituting the above-mentioned adhesive layer at 23°C is preferably 0.02MPa or more, more preferably 0.03MPa or more, particularly preferably 0.04MPa or more, and further preferably 0.07MPa or more. Thus, it is easy to meet the above lower limit of the storage modulus G'(85). In addition, the storage modulus G'(23) is preferably 0.3MPa or less, more preferably 0.15MPa or less, particularly preferably 0.10MPa or less, and further preferably 0.08MPa or less. Thus, it is easy to meet the above upper limit of the storage modulus G'(85).

[0039] The gel fraction of the adhesive constituting the above-mentioned adhesive layer is preferably 10% or more, more preferably 20% or more, particularly preferably 30% or more, and further preferably 40% or more. As a result, the adhesive will exert an appropriate cohesive force that can withstand repeated bending. As a result, the durability is better. On the other hand, the gel fraction of the adhesive of the present embodiment is preferably 90% or less, more preferably 75% or less, particularly preferably 65% ​​or less, further preferably 55% or less, and most preferably 47% or less. Therefore, it is inferred that the residual stress in the adhesive caused by bending decreases, and the durability is better. In addition, the method for measuring the gel fraction of this specification is shown in the test example described later.

[0040] The haze value of the adhesive layer at 23°C is preferably 10% or less, more preferably 5% or less, particularly preferably 1% or less, and further preferably 0.7% or less. When the haze value of the adhesive layer at 23°C is as above, the light transmittance is excellent and it is suitable for use in repeatedly curved displays. The lower limit of the haze value at 23°C is not particularly limited, but is preferably 0% or more, and more preferably 0.1% or more.

[0041] In addition, the haze value of the above-mentioned adhesive layer at -40°C is preferably 10% or less, more preferably 5% or less, particularly preferably 1% or less, and further preferably 0.7% or less. By setting the haze value of the adhesive layer at -40°C to the above, the obtained flexible display can have excellent durability in cold conditions. The lower limit of the haze value at -40°C is not particularly limited, but is preferably 0% or more, and more preferably 0.1% or more. Here, the haze value at -40°C is a value obtained by measuring the adhesive layer after leaving it in an environment of -40°C for 240 hours and then leaving it to stand for 1 hour in an environment of 23°C and 50% RH.

[0042] The haze value is a characteristic value including the thickness of the adhesive layer, and preferably satisfies the haze value regardless of the thickness of the adhesive layer. Here, the haze value in this specification is a value measured in accordance with JIS K7136:2000.

[0043] From the perspective of image / video visibility, the total light transmittance of the adhesive layer at 23°C is preferably 70% or more, more preferably 80% or more, particularly preferably 90% or more, and further preferably 95% or more. The upper limit of the total light transmittance at 23°C is usually 100%. In addition, the total light transmittance of this specification is a value measured in accordance with JIS K7361-1:1997.

[0044] In addition, the total light transmittance of the above-mentioned adhesive layer at -40°C is preferably 70% or more, more preferably 80% or more, particularly preferably 90% or more, and further preferably 95% or more. By setting the total light transmittance of the adhesive layer at -40°C to the above, the obtained flexible display can have excellent durability in cold conditions. On the other hand, the upper limit of the total light transmittance at -40°C is usually 100%. Here, the total light transmittance at -40°C is the value obtained by measuring the adhesive layer after leaving it in an environment of -40°C for 240 hours and then leaving it to stand for 1 hour in an environment of 23°C and 50% RH.

[0045] The specific structure of an example of the adhesive sheet of this embodiment is shown in FIG. Figure 1 .

[0046] like Figure 1 As shown, an adhesive sheet 1 of one embodiment is composed of two release sheets 12a, 12b and an adhesive layer 11, and the adhesive layer 11 is sandwiched by the two release sheets 12a, 12b in a manner of contacting the release surfaces of the two release sheets 12a, 12b. In addition, the release surface of the release sheet in this specification refers to the surface of the release sheet that has release properties, including the surface that has been subjected to release treatment and the surface that has not been subjected to release treatment but still exhibits release properties.

[0047] 1. Constituent elements

[0048] 1-1. Adhesive layer

[0049] The adhesive layer 11 is composed of an adhesive having the above-mentioned physical properties. As long as the above-mentioned physical properties (especially the water vapor permeability and the storage modulus G'(85)) are satisfied, the type of adhesive constituting the adhesive layer 11 is not particularly limited, and for example, it may be any one of an acrylic adhesive (main polymer: acrylic polymer), a polyester adhesive (main polymer: polyester polymer), a polyurethane adhesive (main polymer: polyurethane polymer), a rubber adhesive (main polymer: rubber polymer), a silicone adhesive (main polymer: silicone polymer), etc. In addition, the adhesive may be any one of an emulsion type, a solvent type or a solvent-free type, and may be any one of a cross-linked type or a non-cross-linked type. Among them, an acrylic adhesive that is easy to satisfy the above-mentioned physical properties and has excellent adhesive physical properties, optical properties, etc. is preferred, and a solvent-type acrylic adhesive is particularly preferred.

[0050] The adhesive of the present embodiment is preferably an adhesive containing a polyrotaxane compound, and is particularly preferably an acrylic adhesive containing a polyrotaxane compound. Specifically, it is preferably an adhesive cross-linked by an adhesive composition (hereinafter sometimes referred to as "adhesive composition P") containing a (meth) acrylate polymer (A) (equivalent to the main polymer) and a polyrotaxane compound (B), wherein the adhesive composition preferably further contains a cross-linking agent (C). If it is this adhesive, the above-mentioned physical properties can be met, and it is easy to obtain good adhesion. In addition, in this specification, (meth) acrylic acid refers to both acrylic acid and methacrylic acid. Other similar uses are also the same. In addition, "polymer" also includes the concept of "copolymer".

[0051] (1) Components of the adhesive composition P

[0052] (1-1) (Meth)acrylate polymer (A)

[0053] The (meth)acrylate polymer (A) preferably contains, as monomer units constituting the polymer, an alkyl (meth)acrylate for exhibiting good adhesiveness and a monomer having a reactive functional group serving as a crosslinking point (reactive functional group-containing monomer).

[0054] In addition, the (meth)acrylate polymer (A) preferably contains an aromatic ring-containing monomer as a monomer unit constituting the polymer. As a result, the (meth)acrylate polymer (A) has good compatibility with the polyrotaxane compound (B), and the compatibility can be maintained even in a low temperature environment. Therefore, it is particularly easy to satisfy the haze value at -40°C and the total light transmittance at -40°C.

[0055] Furthermore, the (meth)acrylate polymer (A) preferably contains a nitrogen atom-containing monomer as a monomer unit constituting the polymer. Thus, the reactive functional groups from the reactive functional group-containing monomer are activated, and even if the reactive functional groups are small, crosslinking with the polyrotaxane compound (B) can be more effectively performed. Therefore, the cohesive force and flexibility of the obtained adhesive are improved, and it is easier to meet the above-mentioned storage modulus G'(85) (and storage modulus G'(23)).

[0056] Therefore, the (meth)acrylate polymer (A) preferably contains an alkyl (meth)acrylate, an aromatic ring-containing monomer, and a reactive functional group-containing monomer as monomer units constituting the polymer, and particularly preferably contains an alkyl (meth)acrylate, an aromatic ring-containing monomer, a nitrogen atom-containing monomer, and a reactive functional group-containing monomer as monomer units constituting the polymer.

[0057] As the alkyl (meth)acrylate, preferably one having an alkyl group with carbon atoms of 1 to 20. The alkyl group is preferably linear or branched.

[0058] The (meth)acrylic acid alkyl ester having an alkyl group with 1 to 20 carbon atoms preferably contains a monomer having a glass transition temperature (Tg) of -40°C or less as a homopolymer (hereinafter, sometimes referred to as a "low Tg acrylic acid alkyl ester") and a monomer having a glass transition temperature (Tg) of more than 0°C as a homopolymer (hereinafter, sometimes referred to as a "high Tg acrylic acid alkyl ester"). It is speculated that by containing such low Tg acrylic acid alkyl esters and high Tg acrylic acid alkyl esters as structural monomer units, the conformation of the (meth)acrylic acid ester polymer (A) can be prevented from becoming too small. As a result, the contact points with the polyrotaxane compound (B) are increased, and it is speculated that even if the (meth)acrylic acid ester polymer (A) has only a few cross-linking points, it can form a sufficient cross-linking structure with the polyrotaxane compound (B). Therefore, the obtained adhesive layer can exert good adhesion and is easy to satisfy the above-mentioned storage modulus G'(85).

[0059] As low Tg alkyl acrylates, for example, preferably n-butyl acrylate (Tg-55°C), n-octyl acrylate (Tg-65°C), isooctyl acrylate (Tg-58°C), 2-ethylhexyl acrylate (Tg-70°C), isononyl acrylate (Tg-58°C), isodecyl acrylate (Tg-60°C), isodecyl methacrylate (Tg-41°C), n-undecyl methacrylate (Tg-65°C), tridecyl acrylate (Tg-55°C), tridecyl methacrylate (Tg-40°C), etc. Among them, from the viewpoint of adhesion, as low Tg alkyl acrylates, low Tg alkyl acrylates having a homopolymer Tg of -45°C or less are more preferred, and low Tg alkyl acrylates having a homopolymer Tg of -50°C or less are particularly preferred. Specifically, n-butyl acrylate and 2-ethylhexyl acrylate are particularly preferred. These low Tg alkyl acrylates may be used alone or in combination of two or more.

[0060] As the above-mentioned high Tg alkyl acrylate, for example, methyl acrylate (Tg 10°C), methyl methacrylate (Tg 105°C), ethyl methacrylate (Tg 65°C), n-butyl methacrylate (Tg 20°C), isobutyl methacrylate (Tg 48°C), tert-butyl methacrylate (Tg 107°C), n-octadecyl acrylate (Tg 30°C), n-octadecyl methacrylate (Tg 38°C), etc. can be listed. Among them, methyl acrylate and methyl methacrylate are preferred from the perspective of easily satisfying the storage modulus G'(85). These high Tg alkyl acrylates can be used alone or in combination of two or more. In addition, the above-mentioned high Tg alkyl acrylate does not contain the aromatic ring-containing monomer and the nitrogen atom-containing monomer described later.

[0061] The (meth)acrylate polymer (A) preferably contains 40% by mass or more, particularly preferably 50% by mass or more, and further preferably 60% by mass or more of a low Tg alkyl acrylate as a monomer unit constituting the polymer. In addition, the (meth)acrylate polymer (A) preferably contains 90% by mass or less, particularly preferably 80% by mass or less, and further preferably 75% by mass or less of a low Tg alkyl acrylate as a monomer unit constituting the polymer.

[0062] The (meth)acrylate polymer (A) preferably contains 1% by mass or more, particularly preferably 4% by mass or more, and further preferably 8% by mass or more of a high Tg alkyl acrylate as a monomer unit constituting the polymer. In addition, the (meth)acrylate polymer (A) preferably contains 24% by mass or less, particularly preferably 18% by mass or less, and further preferably 13% by mass or less of a high Tg alkyl acrylate as a monomer unit constituting the polymer.

[0063] The (meth)acrylate polymer (A) preferably contains 45% by mass or more, more preferably 60% by mass or more, particularly preferably 70% by mass or more, and further preferably 75% by mass or more of a (meth)acrylate alkyl ester having an alkyl group with 1 to 20 carbon atoms as a monomer unit constituting the polymer. In addition, it is preferred that the (meth)acrylate alkyl ester is contained in an amount of 94% by mass or less, more preferably 90% by mass or less, particularly preferably 88% by mass or less, and further preferably 83% by mass or less. If the (meth)acrylate alkyl ester having an alkyl group with 1 to 20 carbon atoms is contained in the above amount, suitable adhesion can be imparted to the (meth)acrylate polymer (A), and at the same time, the above storage modulus G' can be easily satisfied.

[0064] Examples of the aromatic ring-containing monomer include phenyl (meth)acrylate, 2-phenylethyl (meth)acrylate, benzyl (meth)acrylate, naphthyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, phenoxybutyl (meth)acrylate, ethoxylated o-phenylphenol acrylate, diethylene glycol phenoxy (meth)acrylate, polyethylene glycol phenoxy (meth)acrylate, biphenyl di(meth)acrylate, pentafluorobenzyl (meth)acrylate, etc. These aromatic ring-containing monomers may be used alone or in combination of two or more.

[0065] The (meth)acrylate copolymer (A) preferably contains 1% by mass or more, more preferably 4% by mass or more, particularly preferably 8% by mass or more, and further preferably 12% by mass or more of an aromatic ring-containing monomer as a monomer unit constituting the polymer. In addition, it is preferred to contain 40% by mass or less, more preferably 30% by mass or less, particularly preferably 23% by mass or less, and further preferably 18% by mass or less of an aromatic ring-containing monomer. By making the content of the aromatic ring-containing monomer within the above range, it is easy to satisfy the above-mentioned haze value and storage modulus G' at -40°C. In addition, the adhesiveness can be well maintained.

[0066] As the nitrogen-containing monomer, there can be listed a monomer having an amino group, a monomer having an amide group, a monomer having a nitrogen-containing heterocyclic ring, etc., among which a monomer having an amino group is preferred. In addition, from the perspective of increasing the degree of freedom of the part derived from the above-mentioned nitrogen-containing monomer in the higher order structure of the adhesive, it is preferred that the nitrogen-containing monomer contains no other reactive unsaturated double bond groups except for one polymerizable group for forming the (meth)acrylate polymer (A). The nitrogen-containing monomer can be used alone or in combination of two or more.

[0067] Examples of the monomer having an amino group include monomethylaminoethyl (meth)acrylate, monoethylaminoethyl (meth)acrylate, monomethylaminopropyl (meth)acrylate, monoethylaminopropyl (meth)acrylate, and dimethylaminoethyl (meth)acrylate.

[0068] Examples of the monomer having an amide group include (meth)acrylamide, N-methyl(meth)acrylamide, N-methylol(meth)acrylamide, N-tert-butyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-ethyl(meth)acrylamide, N,N-dimethylaminopropyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-phenyl(meth)acrylamide, N-(n-butoxymethyl)(meth)acrylamide, dimethylaminopropyl(meth)acrylamide, and N-vinylcaprolactam.

[0069] Examples of monomers having a nitrogen-containing heterocyclic ring include N-(meth)acryloylmorpholine, N-vinyl-2-pyrrolidone, N-(meth)acryloylpyrrolidone, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-(meth)acryloylaziridine, aziridinylethyl (meth)acrylate, 2-vinylpyridine, 4-vinylpyridine, 2-vinylpyrazine, 1-vinylimidazole, N-vinylcarbazole, and N-vinylphthalimide.

[0070] The (meth)acrylate copolymer (A) preferably contains 0.01% by mass or more, more preferably 0.1% by mass or more, particularly preferably 0.3% by mass or more, and further preferably 0.8% by mass or more of a nitrogen-containing monomer as a monomer unit constituting the polymer. In addition, it is preferred to contain 14% by mass or less, more preferably 8% by mass or less, particularly preferably 4% by mass or less, and further preferably 2% by mass or less of a nitrogen-containing monomer. By making the content of the nitrogen-containing monomer within the above range, it is easy to satisfy the above storage modulus G'. In addition, adhesion can also be well maintained.

[0071] Since the (meth)acrylate polymer (A) contains a monomer containing a reactive functional group as a monomer unit constituting the polymer, the reactive functional group from the monomer containing a reactive functional group can react with the crosslinking agent (C) described later to form a crosslinked structure (three-dimensional network structure). Thus, an adhesive having the desired cohesive force and easily satisfying the above-mentioned physical properties can be obtained.

[0072] As the reactive functional group-containing monomer as a monomer unit constituting the (meth)acrylate polymer (A), preferably, there can be mentioned a monomer having a hydroxyl group in the molecule (hydroxyl group-containing monomer), a monomer having a carboxyl group in the molecule (carboxyl group-containing monomer), etc. These reactive functional group-containing monomers may be used alone or in combination of two or more.

[0073] Among the above-mentioned reactive functional group-containing monomers, hydroxyl group-containing monomers or carboxyl group-containing monomers are preferred, and hydroxyl group-containing monomers are particularly preferred. Hydroxyl group-containing monomers are likely to satisfy the above-mentioned physical properties.

[0074] Examples of hydroxyl-containing monomers include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. Among them, hydroxyalkyl (meth)acrylates having a hydroxyalkyl group having 1 to 4 carbon atoms are preferred from the perspective of being easy to satisfy the above-mentioned physical properties. These hydroxyl-containing monomers may be used alone or in combination of two or more.

[0075] Examples of carboxyl-containing monomers include ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, itaconic acid, and citraconic acid. Among them, acrylic acid is preferred from the perspective of the adhesive force of the obtained (meth)acrylate polymer (A). These carboxyl-containing monomers may be used alone or in combination of two or more.

[0076] The (meth)acrylate polymer (A) preferably contains 1% by mass or more, particularly preferably 2% by mass or more, and further preferably 3% by mass or more of a monomer containing a reactive functional group as a monomer unit constituting the polymer. In addition, the (meth)acrylate polymer (A) preferably contains 13% by mass or less, particularly preferably 8% by mass or less, and further preferably 5% by mass or less of a monomer containing a reactive functional group as a monomer unit constituting the polymer. If the (meth)acrylate polymer (A) contains a monomer containing a reactive functional group as a monomer unit in the above amount, the cohesive force of the adhesive obtained by the crosslinking reaction with the crosslinking agent (C) is appropriate, and it is easy to satisfy the above-mentioned storage modulus G'. In addition, it is also easy to satisfy the above-mentioned water vapor permeability.

[0077] In addition, from the perspective of resistance to whitening by wet heat and from the perspective of reducing the storage modulus G' by crosslinking with the polyrotaxane compound (B), it is considered to be beneficial to increase the proportion of the hydroxyl-containing monomer in the (meth)acrylate polymer (A). However, if the proportion of the hydroxyl-containing monomer is increased excessively, the water vapor permeability will increase excessively, and the hydrogen bonds in the adhesive will become very large. It is speculated that the surface of the adhesive layer will become hardened to a degree that will not be reflected in the elastic modulus, thereby causing a decrease in bending resistance.

[0078] The (meth)acrylate polymer (A) preferably does not contain a carboxyl group-containing monomer as a monomer unit constituting the polymer. Since the carboxyl group is an acidic component, by not containing a carboxyl group-containing monomer, when the adhesive is attached to an object that contains a substance that may cause adverse conditions due to acid, such as a transparent conductive film such as tin-doped indium oxide (ITO), or a metal film, a metal mesh, etc., adverse conditions (corrosion, resistance value change, etc.) caused by acid can be suppressed.

[0079] By making the (meth)acrylate polymer (A) contain a hydroxyl group-containing monomer as a reactive functional group-containing monomer constituting the polymer and not containing a carboxyl group-containing monomer, the crosslinking of the (meth)acrylate polymer (A) and the polyrotaxane compound (B) by the crosslinking agent (C) (particularly an isocyanate crosslinking agent) can be more effectively performed. As a result, it is easier to satisfy the above-mentioned storage modulus G'.

[0080] Here, "free of carboxyl-containing monomers" means that carboxyl-containing monomers are substantially free of, and in addition to being completely free of, carboxyl-containing monomers, it is permitted to contain carboxyl-containing monomers to such an extent that corrosion of transparent conductive films or metal wirings does not occur. Specifically, in the (meth)acrylate polymer (A), it is permitted to contain carboxyl-containing monomers as monomer units in an amount of 0.1% by mass or less, preferably 0.01% by mass or less, and more preferably 0.001% by mass or less.

[0081] The (meth)acrylate polymer (A) may contain other monomers as monomer units constituting the polymer as required. As other monomers, in order not to hinder the above-mentioned effects of the monomer containing reactive functional groups, preferably monomers without reactive functional groups. As such monomers, for example, (meth)acrylic acid alkoxyalkyl esters such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate, ethyl acetate, styrene, etc. can be listed. These other monomers can be used alone or in combination of two or more.

[0082] The polymerization form of the (meth)acrylate polymer (A) may be a random copolymer or a block copolymer.

[0083] The weight average molecular weight of the (meth) acrylate polymer (A) is preferably 100,000 or more, more preferably 400,000 or more, particularly preferably 900,000 or more, and further preferably 1.4 million or more. In addition, the weight average molecular weight of the (meth) acrylate polymer (A) is preferably 3 million or less, more preferably 2.3 million or less, particularly preferably 1.8 million or less, and further preferably 1.6 million or less. If the weight average molecular weight of the (meth) acrylate polymer (A) is within the above range, it is easy to satisfy the above-mentioned physical properties. In addition, the weight average molecular weight in this specification is a value converted to standard polystyrene measured by gel permeation chromatography (GPC).

[0084] The glass transition temperature (Tg) of the (meth)acrylate polymer (A) is preferably above -80°C, more preferably above -60°C, particularly preferably above -50°C, and further preferably above -40°C. In addition, the glass transition temperature (Tg) of the (meth)acrylate polymer (A) is preferably below 10°C, more preferably below 0°C, particularly preferably below -10°C, and further preferably below -20°C. If the glass transition temperature (Tg) of the (meth)acrylate polymer (A) is within the above range, it is easy to satisfy the above storage modulus G'. In addition, the glass transition temperature (Tg) of the (meth)acrylate polymer (A) in this specification is calculated based on the glass transition temperature (Tg) of each monomer constituting the (meth)acrylate polymer (A) as a homopolymer, and is obtained by FOX's formula.

[0085] In the adhesive composition P, the (meth)acrylate polymer (A) may be used alone or in combination of two or more.

[0086] (1-2) Polyrotaxane compound (B)

[0087] The polyrotaxane compound (B) is a compound in which a linear molecule penetrates the opening of at least two cyclic molecules and has blocking groups at both ends of the linear molecule. In the polyrotaxane compound (B), the cyclic molecule can move (slide) freely on the linear molecule, but the cyclic molecule cannot be separated from the linear molecule due to the blocking groups. That is, the linear molecule and the cyclic molecule maintain their form not by chemical bonds such as non-covalent bonds but by so-called mechanical bonding.

[0088] Since the adhesive obtained from the adhesive composition P contains such a polyrotaxane compound (B), the stress relaxation property becomes high and it is easy to satisfy the above-mentioned storage modulus G'. In particular, when the adhesive composition P contains a crosslinking agent (C), if the adhesive composition P is crosslinked, the reactive group of the crosslinking agent (C) reacts with the reactive group of the cyclic molecule possessed by the polyrotaxane compound (B) to form a crosslinking agent adduct. In addition, it is speculated that the (meth) acrylate polymer (A) is bonded to a cyclic molecule of the polyrotaxane compound (B) through the crosslinking agent (C) in the crosslinking agent adduct through the reactive functional group of the reactive functional group-containing monomer possessed by the polymer, and similarly, other (meth) acrylate polymers (A) are bonded to other cyclic molecules of the polyrotaxane compound (B). As a result, a structure (crosslinked structure) in which multiple (meth) acrylate polymers (A) are crosslinked to each other via the polyrotaxane compound (B) having the above-mentioned slidable mechanical bond is formed. By having such a cross-linked structure, the stress relaxation property of the obtained adhesive is more excellent and the above-mentioned storage modulus G' is more likely to be satisfied.

[0089] The obtained adhesive does not need to have all the above structures, and may include a structure in which two (meth)acrylate polymers (A) are directly bonded via a crosslinking agent (C) without intermediary of a polyrotaxane compound (B).

[0090] The polyrotaxane compound (B) of the present embodiment preferably has a cyclic molecule containing a reactive group that can react with the reactive group of the crosslinking agent (C). In addition, the reactive group is preferably a hydrophilic functional group. By making the cyclic molecule of the polyrotaxane compound (B) have such a reactive group, it is easy to satisfy the above-mentioned water vapor permeability. As the reactive group, for example, a hydroxyl group, a carboxyl group, etc. can be listed, wherein a hydroxyl group is preferred.

[0091] The polyrotaxane compound (B) of the present embodiment preferably has a cyclic oligosaccharide as a cyclic molecule. The cyclic oligosaccharide has a hydroxyl group as a reactive group in an unmodified state. In addition, by using a cyclic oligosaccharide as the cyclic molecule of the polyrotaxane compound (B), it is possible to select an appropriate ring diameter, thereby, it is easy to show the effect brought about by the movement of the cyclic molecule on the linear molecule. Further, it is also easy to introduce various substituents, etc., thereby, it is possible to adjust the physical properties of the resulting adhesive. Further, if it is a cyclic oligosaccharide, it also has the advantage of being easy to obtain. In addition, in this specification, the "cyclic" of "cyclic molecule" or "cyclic oligosaccharide" refers to basically "cyclic". That is, as long as it can move on a linear molecule, the cyclic molecule may not be completely closed-loop, for example, it may be a helical structure.

[0092] Preferred cyclic oligosaccharides include cyclodextrins such as α-cyclodextrin, β-cyclodextrin, and γ-cyclodextrin, and α-cyclodextrin is particularly preferred. Two or more cyclic molecules of the polyrotaxane compound (B) may be present in the polyrotaxane compound (B) or the adhesive composition P as a mixture.

[0093] The hydroxyl group as a reactive group possessed by the cyclic oligosaccharide may be a hydroxyl group originally present in the cyclic oligosaccharide (referred to as a state before modification), or may be a hydroxyl group introduced into the cyclic oligosaccharide as a substituent.

[0094] The lower limit of the hydroxyl value of the above-mentioned cyclic molecule is preferably more than 10mgKOH / g, more preferably more than 30mgKOH / g, and particularly preferably more than 50mgKOH / g. If the lower limit of the hydroxyl value is as above, the polyrotaxane compound (B) can fully react with the cross-linking agent (C), and a predetermined amount of hydroxyl groups are left, which is easy to satisfy the above-mentioned water vapor permeability. In addition, the upper limit of the hydroxyl value of the above-mentioned cyclic molecule is preferably less than 1000mgKOH / g, more preferably less than 200mgKOH / g, and particularly preferably less than 100mgKOH / g. If the upper limit of the hydroxyl value exceeds the above-mentioned value, since multiple crosslinks will be produced in the same cyclic molecule, the cyclic molecule itself becomes a crosslinking point, and it becomes impossible to play the effect of the crosslinking point as the whole of the polyrotaxane compound (B), and as a result, it may cause the adhesive obtained to be unable to ensure sufficient flexibility.

[0095] The linear molecule of the polyrotaxane compound (B) is not particularly limited as long as it is a molecule or substance that is included in the cyclic molecule and can be integrated by mechanical bonding rather than chemical bonds such as covalent bonds, and is linear. In addition, in this specification, the "linear" of "linear molecule" means basically "linear". That is, as long as the cyclic molecule can move on the linear molecule, the linear molecule may have a branched chain.

[0096] Preferred linear molecules of the polyrotaxane compound (B) include polyethylene glycol, polypropylene glycol, polyisoprene, polyisobutylene, polybutadiene, polytetrahydrofuran, polyacrylate, polydimethylsiloxane, polyethylene, polypropylene, etc. Two or more of these linear molecules may be present in the adhesive composition P as a mixture.

[0097] The lower limit of the number average molecular weight of the linear molecules of the polyrotaxane compound (B) is preferably 3,000 or more, particularly preferably 10,000 or more, and further preferably 20,000 or more. If the lower limit of the number average molecular weight is as above, the amount of movement of the cyclic molecules on the linear molecules can be ensured, and the flexibility of the cross-linked structure of the polyrotaxane compound (B) can be fully obtained. In addition, the upper limit of the number average molecular weight of the linear molecules of the polyrotaxane compound (B) is preferably 300,000 or less, particularly preferably 200,000 or less, and further preferably 100,000 or less. If the upper limit of the number average molecular weight is as above, the solubility of the polyrotaxane compound (B) in the solvent is good.

[0098] The end-capping group of the polyrotaxane compound (B) is not particularly limited as long as it is a group capable of maintaining a state in which cyclic molecules are strung together by linear molecules, and examples of such a group include bulky groups and ionic groups.

[0099] Specifically, the end-capping group of the polyrotaxane compound (B) is preferably a dinitrophenyl group, a cyclodextrin group, an adamantyl group, a trityl group, a fluorescein group, a pyrene group, an anthracene group, or the like, or a main chain or side chain of a polymer having a number average molecular weight of 1,000 to 1,000,000, and two or more of these end-capping groups may be mixed in the polyrotaxane compound (B) or the adhesive composition P.

[0100] The polyrotaxane compound (B) described above can be obtained by a conventionally known method (for example, the method described in Japanese Patent Application Laid-Open No. 2005-154675).

[0101] The content of the polyrotaxane compound (B) in the adhesive composition P of the present embodiment is preferably 1 part by mass or more, more preferably 4 parts by mass or more, particularly preferably 6 parts by mass or more, and further preferably 7 parts by mass or more relative to 100 parts by mass of the (meth) acrylate polymer (A). In addition, the content of the polyrotaxane compound (B) is preferably 30 parts by mass or less, more preferably 24 parts by mass or less, particularly preferably 17 parts by mass or less, and further preferably 12 parts by mass or less. By making the content of the polyrotaxane compound (B) within the above range, it is easy to satisfy both the above-mentioned water vapor permeability and the storage modulus G'.

[0102] (1-3) Cross-linking agent (C)

[0103] The crosslinking agent (C) has a reactive group. The reactive group is preferably a reactive group that can react with the reactive functional group possessed by the (meth) acrylate polymer (A) and the reactive group possessed by the cyclic molecule of the polyrotaxane compound (B). Such a crosslinking agent (C) forms a crosslinking agent adduct with the polyrotaxane compound (B). And the crosslinking agent adduct crosslinks the (meth) acrylate polymer (A) to form a three-dimensional network structure. Thus, the cohesive force of the obtained adhesive is improved, and it is easy to satisfy the above-mentioned physical properties.

[0104] As the above-mentioned crosslinking agent (C), for example, isocyanate crosslinking agents, epoxy crosslinking agents, amine crosslinking agents, melamine crosslinking agents, aziridine crosslinking agents, hydrazine crosslinking agents, aldehyde crosslinking agents, oxazoline crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, ammonium salt crosslinking agents, etc. can be listed. Among them, isocyanate crosslinking agents with high reactivity with hydroxyl groups are preferred. Through isocyanate crosslinking agents, the crosslinking agent addition of the polyrotaxane compound (B) having a hydroxyl group as a reactive group can be fully carried out, thereby, it is easy to meet the above-mentioned water vapor permeability and storage modulus G '. In addition, the crosslinking agent (C) can be used alone or in combination of two or more.

[0105] The isocyanate crosslinking agent contains at least a polyisocyanate compound. Examples of the polyisocyanate compound include aromatic polyisocyanates such as tolylene diisocyanate, diphenylmethane diisocyanate, and xylylene diisocyanate, aliphatic polyisocyanates such as hexamethylene diisocyanate, alicyclic polyisocyanates such as isophorone diisocyanate and hydrogenated diphenylmethane diisocyanate, and biuret bodies and isocyanurate bodies thereof, and adducts thereof as reactants with low molecular weight active hydrogen-containing compounds such as ethylene glycol, propylene glycol, neopentyl glycol, trimethylolpropane, and castor oil.

[0106] The content of the crosslinking agent (C) in the adhesive composition P is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, particularly preferably 1.0 parts by mass or more, and further preferably 1.3 parts by mass or more relative to 100 parts by mass of the (meth)acrylate polymer (A). In addition, the content is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, particularly preferably 2 parts by mass or less, and further preferably 1.8 parts by mass or less. If the content of the crosslinking agent (C) is within the above range, it is easy to satisfy the above physical properties.

[0107] (1-4) Various additives

[0108] In the adhesive composition P, various additives commonly used in acrylic adhesives may be added as needed, such as silane coupling agents, ultraviolet absorbers, antistatic agents, tackifiers, antioxidants, light stabilizers, softeners, fillers, refractive index adjusters, etc. In addition, the polymerization solvent or dilution solvent described later is not included in the additives constituting the adhesive composition P.

[0109] The adhesive composition P preferably contains the above-mentioned silane coupling agent. This improves the adhesion of the obtained adhesive layer to a flexible member as an adherend, and provides more excellent adhesive strength.

[0110] As the silane coupling agent, an organic silicon compound having at least one alkoxysilyl group in the molecule is preferred, and the silane coupling agent has good compatibility with the (meth)acrylate polymer (A) and has light transparency.

[0111] Examples of such silane coupling agents include silicon compounds containing polymerizable unsaturated groups such as vinyl trimethoxysilane, vinyl triethoxysilane, and methacryloxypropyl trimethoxysilane, silicon compounds having epoxy structures such as 3-glycidoxypropyl trimethoxysilane, 3-glycidoxypropyl methyl dimethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, 3-mercaptopropyl trimethoxysilane, 3-mercaptopropyl triethoxysilane, and 3-mercaptopropyl dimethoxymethylsilane. The silane coupling agents may be condensed with a silicon compound containing a mercapto group such as thiol, 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-chloropropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, or a condensate of at least one of these silane coupling agents and a silicon compound containing an alkyl group such as methyltriethoxysilane, ethyltriethoxysilane, methyltrimethoxysilane, or ethyltrimethoxysilane. These silane coupling agents may be used alone or in combination of two or more.

[0112] Relative to 100 parts by mass of (meth) acrylate polymer (A), the content of silane coupling agent in adhesive composition P is preferably 0.01 parts by mass or more, particularly preferably 0.05 parts by mass or more, and more preferably 0.1 parts by mass or more. In addition, the content is preferably 1 part by mass or less, particularly preferably 0.5 parts by mass or less, and more preferably 0.3 parts by mass or less. By making the content of silane coupling agent within the above range, the adhesion of the obtained adhesive layer to the bending member as the adherend is improved, and the adhesion is greater.

[0113] (2) Preparation of Adhesive Composition P

[0114] The adhesive composition P can be prepared by preparing a (meth)acrylate polymer (A), and adding the obtained (meth)acrylate polymer (A), a polyrotaxane compound (B), and, if necessary, a crosslinking agent (C) and additives.

[0115] The (meth)acrylate polymer (A) can be prepared by polymerizing a mixture of monomers constituting the polymer using a conventional free radical polymerization method. The polymerization of the (meth)acrylate polymer (A) is preferably carried out by a solution polymerization method using a polymerization initiator as required. By utilizing a solution polymerization method to polymerize the (meth)acrylate polymer (A), the resulting polymer is easy to be high molecular weight and easy to adjust the molecular weight distribution, and the generation of low molecular weight bodies can be further reduced. Therefore, even when the gel fraction is reduced and the degree of crosslinking is alleviated, it is not easy to cause the deviation of the adhesive due to repeated bending, and it is easy to obtain an adhesive with excellent durability.

[0116] Examples of the polymerization solvent used in the solution polymerization method include ethyl acetate, n-butyl acetate, isobutyl acetate, toluene, acetone, hexane, and methyl ethyl ketone, and two or more thereof may be used simultaneously.

[0117] Examples of the polymerization initiator include azo compounds and organic peroxides, and two or more thereof may be used simultaneously. Examples of the azo compounds include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), 2,2'-azobis(2-methylpropionic acid) dimethyl ester, 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-hydroxymethylpropionitrile), and 2,2'-azobis[2-(2-imidazolin-2-yl)propane].

[0118] Examples of the organic peroxide include benzoyl peroxide, tert-butyl perbenzoate, cumene hydroperoxide, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di(2-ethoxyethyl)peroxydicarbonate, tert-butyl peroxyneodecanoate, tert-butyl peroxypivalate, (3,5,5-trimethylhexanoyl)peroxide, dipropionyl peroxide, and diacetyl peroxide.

[0119] Furthermore, in the above-mentioned polymerization step, by adding a chain transfer agent such as 2-mercaptoethanol, the weight average molecular weight of the obtained polymer can be adjusted.

[0120] After obtaining the (meth)acrylate polymer (A), the polyrotaxane compound (B) and, if necessary, the crosslinking agent (C), additives and a diluting solvent are added to the solution of the (meth)acrylate polymer (A), and the mixture is thoroughly mixed to obtain a solvent-diluted adhesive composition P (coating solution).

[0121] In addition, when any of the above components is used as a solid component or precipitates when mixed with other components in an undiluted state, the component may be dissolved alone or diluted in a diluting solvent before mixing with other components.

[0122] As the above-mentioned diluting solvent, for example, aliphatic hydrocarbons such as hexane, heptane, and cyclohexane, aromatic hydrocarbons such as toluene and xylene, halogenated hydrocarbons such as dichloromethane and ethylene chloride, alcohols such as methanol, ethanol, propanol, butanol, and 1-methoxy-2-propanol, ketones such as acetone, methyl ethyl ketone, 2-pentanone, isophorone, and cyclohexanone, esters such as ethyl acetate and butyl acetate, and cellosolve-type solvents such as ethyl cellosolve can be used.

[0123] The concentration and viscosity of the coating liquid prepared in the above manner are not particularly limited as long as they are within the range that can be coated, and can be appropriately selected according to the circumstances. For example, the adhesive composition P can be diluted in a manner such that the concentration is 10 to 60% by mass. In addition, when obtaining the coating liquid, the addition of a diluting solvent or the like is not a necessary condition, and as long as the adhesive composition P is a viscosity that can be coated, the diluting solvent may not be added. At this time, the adhesive composition P is a coating liquid in which the polymerization solvent of the (meth)acrylate polymer (A) is directly used as the diluting solvent.

[0124] (3) Preparation of adhesive

[0125] The adhesive constituting the adhesive layer 11 of the present embodiment is preferably formed by cross-linking the adhesive composition P. The cross-linking of the adhesive composition P can usually be performed by heat treatment. In addition, the drying process when the diluting solvent or the like is volatilized from the coating film of the adhesive composition P applied on the desired object can also be used as the heating process.

[0126] The heating temperature of the heat treatment is preferably 50 to 150° C., particularly preferably 70 to 120° C. The heating time is preferably 10 seconds to 10 minutes, particularly preferably 50 seconds to 2 minutes.

[0127] After the heat treatment, a 1-2 week aging period may be provided at room temperature (e.g., 23° C., 50% RH) as required. If the aging period is required, the adhesive is formed after the aging period, and if the aging period is not required, the adhesive is formed after the heat treatment is completed.

[0128] When the adhesive composition P contains a crosslinking agent (C), the (meth)acrylate polymer (A) and the polyrotaxane compound (B) are crosslinked via the crosslinking agent (C) by the above-mentioned heat treatment (and aging) to form a crosslinked structure, thereby obtaining an adhesive.

[0129] (4) Thickness of adhesive layer

[0130] The lower limit of the thickness of the adhesive layer 11 of the adhesive sheet 1 of the present embodiment (value measured according to JIS K7130) is preferably 1 μm or more, more preferably 5 μm or more, particularly preferably 10 μm or more, and further preferably 15 μm or more. If the lower limit of the thickness of the adhesive layer 11 is the above value, it is easy to exert the required adhesive force and the durability is more excellent.

[0131] In addition, the upper limit of the thickness of the adhesive layer 11 is preferably 300 μm or less, more preferably 150 μm or less, and particularly preferably 90 μm or less. From the perspective of being able to obtain a thinner repeatedly bent device, it is further preferably 40 μm or less. If the upper limit of the thickness of the adhesive layer 11 is the above value, the problem of excessive stress generated in the adhesive layer due to repeated bending can be suppressed, and the durability is more excellent. In addition, the adhesive layer 11 can be formed as a single layer or can be formed by stacking multiple layers.

[0132] 1-2. Peel off sheet

[0133] The release sheets 12a and 12b protect the adhesive layer 11 until the adhesive sheet 1 is used, and are peeled off when the adhesive sheet 1 (adhesive layer 11) is used. In the adhesive sheet 1 of the present embodiment, one or both of the release sheets 12a and 12b are not necessarily required.

[0134] As the peeling sheets 12a and 12b, for example, polyethylene film, polypropylene film, polybutylene film, polybutadiene film, polymethylpentene film, polyvinyl chloride film, vinyl chloride copolymer film, polyethylene terephthalate film, polyethylene naphthalate film, polybutylene terephthalate film, polyurethane film, ethylene vinyl acetate film, ionomer resin film, ethylene-(methyl) acrylic acid copolymer film, ethylene-(methyl) acrylic acid ester copolymer film, polystyrene film, polycarbonate film, polyimide film, fluororesin film, etc. can be used. In addition, crosslinked films of these films can also be used. Further, laminated films of these films can also be used.

[0135] It is preferred that the release surface of the release sheets 12a and 12b (particularly the surface in contact with the adhesive layer 11) be subjected to a release treatment. Examples of release agents used for the release treatment include alkyd, silicone, fluorine, unsaturated polyester, polyolefin, and wax release agents. In addition, it is preferred that one of the release sheets 12a and 12b be a heavy release type release sheet with a large release force, and the other be a light release type release sheet with a small release force.

[0136] The thickness of the release sheets 12a and 12b is not particularly limited, but is generally about 20 to 150 μm.

[0137] 2.Physical properties

[0138] (1) Adhesion

[0139] The lower limit of the adhesive force of the adhesive sheet 1 of the present embodiment to the soda-lime glass is preferably 0.1N / 25mm or more, more preferably 1N / 25mm or more, particularly preferably 3N / 25mm or more, and further preferably 4.5N / 25mm or more. If the lower limit of the adhesive force of the adhesive sheet 1 to the soda-lime glass is as above, the durability is more excellent. On the other hand, the upper limit of the above-mentioned adhesion is not particularly limited, but sometimes reoperability is required. From this perspective, the above-mentioned adhesion is preferably 60N / 25mm or less, more preferably 30N / 25mm or less, and particularly preferably 10N / 25mm or less. In addition, the adhesion in this specification refers to the adhesion measured by the 180-degree peeling method according to JIS Z0237:2009, and the specific test method is shown in the test example described later.

[0140] (2) CIE1976L * a * b * Color System

[0141] The CIE 1976L * a * b * Lightness L specified by the color system * It is preferably 60 or more, more preferably 70 or more, particularly preferably 80 or more, and further preferably 90 or more. * It is preferably 100 or less, more preferably 99 or less, and particularly preferably 98 or less. The chromaticity a of the adhesive layer 11 * The absolute value of is preferably 0 or more, particularly preferably 0.1 or more, and further preferably 0.2 or more. * The absolute value of is preferably 0.8 or less, particularly preferably 0.6 or less, and further preferably 0.4 or less. The chromaticity b of the adhesive layer 11 is *The absolute value of is preferably 0 or more, particularly preferably 0.1 or more, and further preferably 0.2 or more. * The absolute value of is preferably 0.8 or less, particularly preferably 0.6 or less, and further preferably 0.4 or less. Thus, the adhesive layer 11 can have a color tone suitable for repeatedly bending a display. * 、Chroma a * and b * The measuring method is shown in the test examples described later.

[0142] 3. Preparation of Adhesive Sheets

[0143] As a manufacturing example of the adhesive sheet 1, the case of using the above-mentioned adhesive composition P is described. A coating liquid of the adhesive composition P is applied to the release surface of a release sheet 12a (or 12b), and a heat treatment is performed to thermally crosslink the adhesive composition P to form a coating layer, and then the release surface of another release sheet 12b (or 12a) is overlapped on the coating layer. When a aging period is required, the above-mentioned coating layer forms an adhesive layer 11 by setting a aging period. When a aging period is not required, the above-mentioned coating layer directly forms an adhesive layer 11. Thus, the above-mentioned adhesive sheet 1 is obtained. The conditions for the heating treatment and aging are as described above.

[0144] As another manufacturing example of the adhesive sheet 1, a coating liquid of an adhesive composition P is applied to the release surface of a release sheet 12a, and a heat treatment is performed to thermally crosslink the adhesive composition P and form a coating layer, thereby obtaining a release sheet 12a with a coating layer. In addition, a coating liquid of the above-mentioned adhesive composition P is applied to the release surface of another release sheet 12b, and a heat treatment is performed to thermally crosslink the adhesive composition P and form a coating layer, thereby obtaining a release sheet 12b with a coating layer. Then, the release sheet 12a with a coating layer and the release sheet 12b with a coating layer are attached in such a manner that the two coating layers are in contact with each other. When a maturation period is required, the above-mentioned laminated coating layer forms an adhesive layer 11 by setting a maturation period, and when a maturation period is not required, the above-mentioned laminated coating layer directly forms an adhesive layer 11. Thus, the above-mentioned adhesive sheet 1 is obtained. Through this manufacturing example, even when the adhesive layer 11 is thick, it can be stably manufactured.

[0145] As a method for applying the coating liquid of the adhesive composition P, for example, a bar coating method, a knife coating method, a roll coating method, a blade coating method, a die coating method, a gravure coating method, etc. can be used.

[0146] [Repeated bending of laminated members]

[0147] like Figure 2As shown, the repeatedly bent laminated member 2 of this embodiment is composed of a first bending member 21 (one bending member), a second bending member 22 (another bending member) and an adhesive layer 11, and the adhesive layer 11 is located between the first bending member 21 and the second bending member 22 and adheres the first bending member 21 and the second bending member 22 to each other.

[0148] The adhesive layer 11 in the repeatedly bent laminated member 2 is the adhesive layer 11 of the adhesive sheet 1 described above.

[0149] The repeatedly bent laminated member 2 is a repeatedly bent device itself, or a member constituting a part of a repeatedly bent device. The repeatedly bent device is preferably a display (repeatedly bent display) that can be repeatedly bent (including folded), but is not limited thereto. Examples of the repeatedly bent device include organic electroluminescent (organic EL) displays, electrophoretic displays (electronic paper), liquid crystal displays using plastic substrates (films) as substrates, foldable displays, and the like, and may also be touch panels.

[0150] The first flexible member 21 and the second flexible member 22 are members that can be bent repeatedly (including folding), and examples thereof include coatings, gas barrier films, hard coatings, polarizing films (polarizers), polarizers, phase difference films (phase difference plates), viewing angle compensation films, brightness enhancement films, contrast enhancement films, diffusion films, semi-transmitting reflective films, electrode films, transparent conductive films, metal mesh films, flexible glass, film sensors (touch sensing films), liquid crystal polymer films, light-emitting polymer films, film-like liquid crystal modules, organic EL modules (organic EL films, organic EL elements), electronic paper modules (film-like electronic paper), TFT (Thin Film Transistor) substrates, etc.

[0151] At least one of the first bending member 21 and the second bending member 22 may be a polyimide film, or a laminate having a polyimide film on the side of the adhesive layer 11. Polyimide films generally have low adhesion to adhesive layers, but according to the adhesive layer 11 of this embodiment, even if the polyimide film is an adherend, excellent durability can be obtained.

[0152] The Young's modulus of the first bending member 21 and the second bending member 22 are preferably 0.1 to 10 GPa, particularly preferably 0.5 to 7 GPa, and further preferably 1.0 to 5 GPa. When the Young's modulus of the first bending member 21 and the second bending member 22 are within this range, each bending member can be easily bent repeatedly.

[0153] Furthermore, when the first bending member 21 and the second bending member 22 are bent along their center lines, the angle at which they are bent without cracking or irreversible deformation (bending angle on the acute angle formed by the surface of the bending member) is preferably 150° or less, more preferably 90° or less, particularly preferably 60° or less, further preferably 30° or less, and most preferably 10° or less. Thus, the repeatedly bendable device described later can be easily obtained.

[0154] The thickness of the first bending member 21 and the second bending member 22 is preferably 10 to 3000 μm, particularly preferably 25 to 1000 μm, and further preferably 50 to 500 μm. When the thickness of the first bending member 21 and the second bending member 22 is within this range, each bending member can be easily bent repeatedly.

[0155] When the repeatedly bent laminated member 2 is manufactured, as an example, one release sheet 12 a of the adhesive sheet 1 is peeled off, and the exposed adhesive layer 11 of the adhesive sheet 1 is bonded to one surface of the first bending member 21 .

[0156] Then, another release sheet 12b is peeled off from the adhesive layer 11 of the adhesive sheet 1, and the exposed adhesive layer 11 of the adhesive sheet 1 is bonded to the second bending member 22 to obtain the repeatedly bent laminated member 2. In another example, the bonding order of the first bending member 21 and the second bending member 22 may be changed.

[0157] [Repeated bending of the device]

[0158] The repeatedly-bending device of this embodiment includes the repeatedly-bending laminated member 2, and the device may be composed of only the repeatedly-bending laminated member 2, or may be composed of one or more repeatedly-bending laminated members 2 and other flexible members. When stacking one repeatedly-bending laminated member 2 with another repeatedly-bending laminated member 2, or stacking a repeatedly-bending laminated member 2 with other flexible members, it is preferred that the stacking be performed via the adhesive layer 11 of the adhesive sheet 1.

[0159] The adhesive layer of the repeatedly bending device of this embodiment is composed of the above-mentioned adhesive. Therefore, when it is repeatedly bent or kept in a bent state for a long time, it is not easy for the adhesive layer in the bent part to peel off at the interface between the adherend and the adhesive layer, and light leakage and visibility reduction caused by bending can be suppressed.

[0160] A repeatedly bent device as an example of this embodiment is shown in FIG. Figure 3 In addition, the repeatedly bent device of the present invention is not limited to the repeatedly bent device.

[0161] like Figure 3As shown, the repeatedly bending device 3 of this embodiment is composed of a cover film 31, a first adhesive layer 32, a polarizing film 33, a second adhesive layer 34, a touch sensing film 35, a third adhesive layer 36, an organic EL element 37, a fourth adhesive layer 38, and a TFT substrate 39 stacked in order from the top. The cover film 31, the polarizing film 33, the touch sensing film 35, the organic EL element 37, and the TFT substrate 39 are equivalent to the bending member.

[0162] At least one of the first adhesive layer 32, the second adhesive layer 34, the third adhesive layer 36, and the fourth adhesive layer 38 is the adhesive layer 11 of the adhesive sheet 1. Preferably, any two or more of the first adhesive layer 32, the second adhesive layer 34, the third adhesive layer 36, and the fourth adhesive layer 38 are the adhesive layers 11 of the adhesive sheet 1, and most preferably, the adhesive layers 32, 34, 36, and 38 are all the adhesive layers 11 of the adhesive sheet 1.

[0163] Here, for example, when the TFT substrate 39 includes a polyimide film, and particularly when the fourth adhesive layer 38 side includes a polyimide film, it is preferred that at least the fourth adhesive layer 38 is the adhesive layer 11 of the adhesive sheet 1 described above.

[0164] The embodiments described above are described to facilitate understanding of the present invention, and are not described to limit the present invention. Therefore, each element disclosed in the above embodiments also includes all design changes or equivalents within the technical scope of the present invention.

[0165] For example, one or both of the release sheets 12a and 12b in the adhesive sheet 1 may be omitted, and a desired flexible member may be laminated instead of the release sheets 12a and / or 12b.

[0166] Example

[0167] Hereinafter, the present invention will be described in further detail with reference to Examples and the like, but the scope of the present invention is not limited to these Examples and the like.

[0168] [Example 1]

[0169] 1. Preparation of (meth)acrylate polymer (A)

[0170] 70 parts by mass of n-butyl acrylate, 10 parts by mass of methyl acrylate, 15 parts by mass of 2-phenoxyethyl acrylate, 1 part by mass of dimethylaminoethyl acrylate and 4 parts by mass of 2-hydroxyethyl acrylate were copolymerized by solution polymerization to prepare a (meth)acrylate polymer (A). The molecular weight of the (meth)acrylate polymer (A) was measured by the method described below, and the weight average molecular weight (Mw) was 1.5 million. In addition, the glass transition temperature (Tg) of the (meth)acrylate polymer (A) calculated by the FOX formula was -35°C.

[0171] 2. Preparation of adhesive composition

[0172] 100 parts by mass (solid content conversion value; the same below) of the (meth)acrylate polymer (A) obtained in the above step 1, 5.0 parts by mass of a polyrotaxane compound (B) (manufactured by Advanced Softmaterials Inc., product name "SeRM Super Polymer SH3400P", linear molecule: polyethylene glycol, cyclic molecule: α-cyclodextrin having hydroxypropyl and caprolactone chains, end-capping group: adamantyl, weight average molecular weight (Mw) 700,000, hydroxyl value 72 mgKOH / g), 1.5 parts by mass of trimethylolpropane-modified xylylene diisocyanate as a crosslinking agent (C) (manufactured by Soken Chemical & Engineering Co., Ltd., product name "TD-75"), and 0.17 parts by mass of 3-glycidoxypropyltrimethoxysilane as a silane coupling agent are mixed, stirred thoroughly, and diluted with methyl ethyl ketone to obtain a coating liquid of an adhesive composition.

[0173] 3. Manufacturing of adhesive sheet

[0174] The coating liquid of the obtained adhesive composition was applied to the release-treated surface of a heavy-release release sheet (manufactured by Lintec Corporation, product name "SP-PET752150") having one side of a polyethylene terephthalate film subjected to release treatment with a silicone release agent using a knife coater. The coating layer was then heated at 90° C. for 1 minute to form a coating layer.

[0175] Next, the coating layer on the heavy release type release sheet obtained above and the light release type release sheet (manufactured by Lintec Corporation, product name "SP-PET381130") on which one side of the polyethylene terephthalate film was subjected to release treatment using a silicone release agent were laminated so that the release treated surface of the light release type release sheet was in contact with the coating layer, and aged for 7 days at 23°C and 50% RH to obtain an adhesive sheet having an adhesive layer with a thickness of 25 μm, that is, an adhesive sheet having a structure of heavy release type release sheet / adhesive layer (thickness: 25 μm) / light release type release sheet. In addition, the thickness of the adhesive layer is a value measured in accordance with JIS K7130 using a constant pressure thickness gauge (manufactured by TECLOCK Co., Ltd., product name "PG-02").

[0176] Here, each compounding ratio (solid content conversion value) of the adhesive composition when the (meth)acrylate polymer (A) is 100 parts by mass (solid content conversion value) is shown in Table 1. In addition, the details of the abbreviations and the like described in Table 1 are as follows.

[0177] [(Meth)acrylate polymer (A)]

[0178] BA: n-butyl acrylate

[0179] MA: Methyl acrylate

[0180] PhEA: 2-Phenoxyethyl acrylate

[0181] DMAEA: Dimethylaminoethyl acrylate

[0182] HEA: 2-Hydroxyethyl Acrylate

[0183] [Examples 2 to 6, Comparative Examples 1 to 2]

[0184] An adhesive sheet was produced in the same manner as in Example 1 except that the type and ratio of each monomer constituting the (meth)acrylate polymer (A), the weight average molecular weight (Mw) of the (meth)acrylate polymer (A), the blending amount of the polyrotaxane compound (B), the blending amount of the crosslinking agent (C), and the thickness of the adhesive layer were changed as shown in Table 1. The glass transition temperature (Tg) of the (meth)acrylate polymer (A) in each example calculated by the FOX equation is shown in Table 1.

[0185] [Test Example 1] (Measurement of gel fraction)

[0186] The adhesive sheets prepared in the examples and comparative examples were cut into a size of 80 mm × 80 mm, and the adhesive layer was wrapped in a polyester mesh (product name: Tetoron mesh #200). The mass was weighed using a precision balance, and the mass of the mesh alone was subtracted to calculate the mass of the adhesive itself. The mass at this time was recorded as M1.

[0187] Next, the adhesive wrapped in the polyester net is immersed in ethyl acetate at room temperature (23°C) for 24 hours. Then, the adhesive is taken out and air-dried for 24 hours in an environment of 23°C and 50% relative humidity, and further dried in an oven at 80°C for 12 hours. After drying, its mass is weighed with a precision balance, and the mass of the net alone is subtracted to calculate the mass of the adhesive itself. The mass at this time is recorded as M2. The gel fraction (%) is expressed as (M2 / M1)×100.

[0188] The results are shown in Table 2.

[0189] [Test Example 2] (Measurement of water vapor transmission rate)

[0190] The adhesive layer of the adhesive sheet obtained in the embodiment and the comparative example was stacked and made into 100 μm thick. The above adhesive layer with a thickness of 100 μm was sandwiched between two pieces of Tetoron mesh #380, and the water vapor transmission rate (g / (m 2 The results are shown in Table 2.

[0191] [Test Example 3] (Measurement of storage modulus G')

[0192] The adhesive layers of the adhesive sheets prepared in Examples and Comparative Examples were stacked in multiple layers to produce a laminate with a thickness of 3 mm. A cylinder with a diameter of 8 mm (height of 3 mm) was punched out from the obtained laminate of adhesive layers and used as a sample.

[0193] The storage modulus G' of the above sample was measured under the following conditions using a viscoelasticity measuring apparatus (manufactured by Anton Paar, product name "MCR302") in accordance with JIS K7244-1 by a torsional shear method to obtain a storage modulus G'(23) at 23°C and a storage modulus G'(85) at 85°C (MPa). The results are shown in Table 2.

[0194] Measuring frequency: 1Hz

[0195] Measuring temperature: -20℃~150℃

[0196] [Test Example 4] (Measurement of Haze Value)

[0197] The adhesive layer of the adhesive sheet prepared in the examples and comparative examples was bonded to glass to serve as a sample for measurement. Based on background measurement on glass, the haze value (total light haze value; %) at 23°C was measured using a haze meter (manufactured by NIPPON DENSHOKU INDUSTRIES Co., LTD, product name "NDH-5000") according to JIS K7136:2000. The results are shown in Table 2.

[0198] Furthermore, the sample for measurement was left at -40°C for 240 hours and then left at 23°C and 50% RH for 1 hour. The haze value (haze value at -40°C; %) was measured in the same manner as above. The results are shown in Table 2.

[0199] [Test Example 5] (Measurement of total light transmittance)

[0200] The adhesive layer of the adhesive sheet prepared in the examples and comparative examples was bonded to glass to serve as a sample for measurement. Based on the background measurement using glass, the total light transmittance (%) at 23°C was measured for the sample for measurement using a haze meter (manufactured by NIPPON DENSHOKU INDUSTRIES Co., LTD, product name "SH-7000") in accordance with JIS K7361-1:1997. The results are shown in Table 2.

[0201] Furthermore, the above-mentioned sample for measurement was placed in an environment of -40°C for 240 hours, and then placed in an environment of 23°C and 50% RH for 1 hour. Then, the total light transmittance (total light transmittance at -40°C; %) was measured in the same manner as above. The results are shown in Table 2.

[0202] [Test Example 6] (L * a * b * Determination of

[0203] The adhesive layers of the adhesive sheets prepared in Examples and Comparative Examples were measured for CIE 1976 L using a simultaneous photometric spectrophotometer (manufactured by NIPPON DENSHOKU INDUSTRIES CO., LTD., product name "SQ2000"). * a * b * Lightness L specified in the color system * 、Chroma a *and chromaticity b * The results are shown in Table 2.

[0204] [Test Example 7] (Measurement of Adhesion Strength)

[0205] The light release type release sheet was peeled off from the adhesive sheet prepared in the examples and comparative examples, and the exposed adhesive layer was attached to the easy adhesive layer of a polyethylene terephthalate (PET) film (manufactured by TOYOBO CO., LTD., product name "PET A4300", thickness: 100 μm) having an easy adhesive layer to obtain a laminate of a heavy release type release sheet / adhesive layer / PET film. The obtained laminate was cut into a width of 25 mm and a length of 110 mm.

[0206] Under the environment of 23 ℃ and 50% RH, the heavy peeling type peeling sheet was peeled off from the above-mentioned laminate, and the exposed adhesive layer was attached to a soda-lime glass plate (manufactured by Nippon Sheet Glass Co., Ltd., product name "soda-lime glass" thickness: 1.1mm), and an autoclave manufactured by Kurihara Manufacturing Co., Ltd. was used to pressurize for 20 minutes at 0.5MPa at 50 ℃. Then, after being placed under the conditions of 23 ℃ and 50% RH for 24 hours, a tensile testing machine (manufactured by ORIENTEC Co., LTD., TENSILON) was used to measure the adhesion (N / 25mm) when the laminate of the PET film and the adhesive layer was peeled off from the adherend under the conditions of a peeling speed of 300mm / min and a peeling angle of 180 degrees. The conditions other than those described herein were measured in accordance with JIS Z0237:2009. The results are shown in Table 2.

[0207] [Test Example 8] (Evaluation of static durability)

[0208] Under the environment of 23°C and 50% RH, the light peeling type release sheet is peeled off from the adhesive sheet obtained in the embodiment and the comparative example, and the exposed adhesive layer is bonded to one surface of a polyimide (PI) film (manufactured by DU PONT-TORAY CO., LTD., product name "KAPTON 100PI", thickness: 25μm, Young's modulus: 3.4GPa). Then, the heavy peeling type release sheet is peeled off, and the exposed adhesive layer is bonded to the same PI film. Next, an autoclave manufactured by Kurihara Manufacturing Co., Ltd. is used to pressurize at 0.5MPa and 50°C for 20 minutes, and then placed at 23°C and 50% RH for 24 hours. The laminate consisting of PI film / adhesive layer / PI film thus obtained is cut into a width of 50mm and a length of 200mm, and used as a sample.

[0209] In an environment of 85°C, Figure 4As shown, the obtained sample is kept in a bent state between two holding plates (distance between each other: 3mm) composed of two vertically arranged glass plates for 24 hours. After the static bending test, it is visually confirmed whether peeling occurs at the interface between the adhesive layer of the bent portion of the test piece and the adherend. In addition, 10 samples are evaluated in each example. The results are shown in Table 3.

[0210] ◎: No peeling occurred in any of the 10 samples

[0211] ○: 9 to 5 samples did not peel off

[0212] △: 4 to 2 samples did not peel off

[0213] ×: 9 or more samples peeled off

[0214] [Test Example 9] (Evaluation of dynamic durability)

[0215] The laminate consisting of PI film / adhesive layer / PI film obtained in the same manner as in Example 8 was cut into 150 mm×50 mm pieces and used as test pieces. Figure 5 As shown in FIG. 1 , the two ends of the obtained test piece were fixed to two holding plates of a flat body unloaded U-shaped telescopic tester (manufactured by YUASA SYSTEM Co., Ltd., product name "DLDMLH-FS"). Then, the test piece was subjected to a test under an environment of 85°C and 50% RH. The test piece was bent 30,000 times with a bending diameter of 80 mm, a stroke of 80 mm, and a bending speed of 30 rpm.

[0216] After the dynamic bending test, it was visually confirmed whether peeling occurred at the interface between the adhesive layer and the adherend at the bent portion of the test piece. In addition, 10 samples were evaluated in each case. The results are shown in Table 3.

[0217] ◎: No peeling occurred in any of the 10 samples

[0218] 0: 9 to 5 samples did not peel off

[0219] △: 4 to 2 samples did not peel off

[0220] ×: 9 or more samples peeled off

[0221] [Test Example 10] (Evaluation of resistance to wet heat whitening)

[0222] The adhesive layer of the adhesive sheet prepared in the examples and comparative examples was sandwiched between 1.1 mm thick alkali-free glass plates (water vapor transmission rate: 0.0006 g / (m 2·24h)) and a plastic plate with a thickness of 0.7 mm (manufactured by Mitsubishi Rayon Co., Ltd., product name "Acrylite MR-200", water vapor transmission rate 44 g / (m 2 The obtained sample was subjected to autoclaving for 20 minutes at 50°C and 0.5 MPa, and then placed at normal pressure, 23°C, and 50% RH for 24 hours.

[0223] The haze value (haze value before the durability test; %) of the above sample was measured using a haze meter (manufactured by NIPPON DENSHOKU INDUSTRIES CO., LTD., product name "NDH-5000") in accordance with JIS K7136:2000.

[0224] The sample was then stored at 85°C, 85% RH for 1000 hours (durability test), and then placed at 23°C, 50% RH for 24 hours. The haze value of the sample was measured in the same manner as above (haze value after durability test; %).

[0225] The wet heat whitening resistance was evaluated based on the difference in haze values ​​measured before and after the durability test according to the following criteria.

[0226] ◎…The difference in haze value is less than 1.5.

[0227] ○ ...The difference in haze value is 1.5 or more and less than 8.0.

[0228] ×...The difference in haze value is 8.0 or more.

[0229] [Table 1]

[0230]

[0231] [Table 2]

[0232]

[0233] [Table 3]

[0234] Static durability Dynamic durability Resistance to heat and humidity whitening Example 1 ◎ ◎ 〇 Example 2 ◎ ◎ ◎ Example 3 ◎ ◎ ◎ Example 4 〇 ◎ ◎ Example 5 〇 ◎ ◎ Example 6 △ △ 〇 Comparative Example 1 △ △ × Comparative Example 2 × × 〇

[0235] As shown in Table 3, the adhesive layer of the adhesive sheet of the embodiment has excellent durability, and the adhesive layer does not peel off at the interface between the adhesive layer and the flexible member when the two flexible members are bonded and bent for a long time, or when the members are bent repeatedly. In addition, the adhesive layer of the adhesive sheet of the embodiment also has excellent resistance to whitening due to moisture and heat.

[0236] Industrial Applicability

[0237] The present invention is suitable for bonding one bending member and another bending member constituting a repeatedly bending device.

Claims

1. An adhesive sheet having an adhesive layer, wherein the adhesive layer is used to bond one bending member and another bending member constituting a repeatedly bending device, characterized in that: The adhesive layer having a thickness of 100 μm was sandwiched between two sheets of Tetoron mesh #380 and the water vapor permeability measured at 40° C. and 90% RH in accordance with JIS K7129 was 150 g / (m 2 ·24h) or more, The adhesive constituting the adhesive layer has a storage modulus G'(85) at 85° C. of 0.02 MPa or more and 0.2 MPa or less, The adhesive constituting the adhesive layer is an adhesive formed by cross-linking an adhesive composition containing a (meth)acrylate polymer and a polyrotaxane compound. The (meth)acrylate polymer contains 1% by mass to 40% by mass of an aromatic ring-containing monomer as a monomer unit constituting the polymer.

2. The adhesive sheet according to claim 1, characterized in that The adhesive constituting the adhesive layer has a gel fraction of 10% to 90%.

3. The adhesive sheet according to claim 1, characterized in that The adhesive layer has a haze value of 10% or less at 23°C.

4. The adhesive sheet according to claim 1, characterized in that The pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer has a storage modulus G′(23) at 23° C. of 0.02 MPa to 0.3 MPa.

5. The adhesive sheet according to claim 1, characterized in that The adhesive constituting the adhesive layer is an acrylic adhesive.

6. The adhesive sheet according to claim 1, wherein The adhesive sheet has two release sheets. The adhesive layer is sandwiched between the two release sheets so as to be in contact with the release surfaces of the two release sheets.

7. A repeatedly-bending laminated member comprising one flexible member and another flexible member constituting a repeatedly-bending device, and an adhesive layer for bonding the one flexible member and the other flexible member to each other, characterized in that: The adhesive layer is composed of the adhesive layer of the adhesive sheet according to any one of claims 1 to 6.

8. A repeatedly bent device, characterized in that: The device comprises the repeatedly bent laminated structure according to claim 7.

Citation Information

Patent Citations

  • Polyrotaxane and its manufacturing method

    JP2005154675A

  • Adhesive composition, adhesive layer, adhesive sheet, optical member with adhesive layer, and image display device

    JP2016155911A

  • Adhesive sheet

    CN102245726A

  • Adhesive sheet and display

    CN106433498A

  • Optical laminated body and organic electroluminescence display device using same

    WO2017086338A1